Моделі інституціоналізації структурно-інноваційних трансформацій в умовах реформування національної економіки - Сибірцев, В. В.; Sybirtsev, V. (Харківський національний педагогічний університет імені Г. С. Сковороди, 2015)
Досліджено основні засади інституціоналізації структурно-інноваційних трансформацій національної економіки. Обґрунтовано та визначено особливості функціонування сучасних механізмів інституціоналізації структурно-інноваційних трансформацій. Узагальнено передумови, чинники та принципи ефективної інституціоналізації як першооснови сталого розвитку національної економіки. Встановлено особливості сучасного етапу інституціональних перетворень в Україні в контексті тенденцій реалізації інституціональних змін в інших країнах з трансформаційною економікою. Обґрунтовано теоретичні положення щодо перспектив інституціоналізації структурно-інноваційних трансформацій в умовах здійснення процесів реформування національної економіки. Встановлено склад вимог щодо забезпечення ефективності інституціональних перетворень національної економіки. Визначено пріоритети удосконалення механізму вибору інституціональної політики у сфері державного регулювання економічного розвитку. The work abstracted basic principles of institutionalization of innovative structural transformation of the national economy. Author grounded and determined peculiarities of modern mechanisms of institutionalization of structural transformation and innovation. Also it was summarized background, factors and principles of effective institutionalization as a fundamental principle of sustainable development of the national economy. And it was established features of the present stage of institutional transformations in Ukraine in the context of trends in the implementation of institutional changes in other countries in the transformational economy. It was grounded theoretical propositions about the prospects for the institutionalization of structural and innovative transformation in the conditions of the process of reforming the national economy. And it was established the composition of the requirements for ensuring the effectiveness of the institutional transformation of the national economy. And finally it was identified priorities of improvement of the mechanism of choice of the institutional policy of state regulation of economic development.
Models of institutionalization of structural and innovation transformations in the context of reforming the national economy
Keywords: національна економіка; структурно-інноваційні трансформації; інституціональні зміни; реформування; national economy; innovative structural transformation; institutional transformations; reforming